DEFICIT SPENDING DAN PENGARUHNYA TERHADAP PENDAPATAN NASIONAL DAN INFLASI - Daryono Soebagiyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Creating primary money to maintain national product growth performance can pass deficit spending policy and pushing the building of the models can get macroeconomics policy. However, this policy influences inflation, therefore real value of wealth in society properties is decreased. Hence, the deficit spending policy can be passed by printing much money to raise welfare cost can be calculated.